2019
DOI: 10.1038/s41467-019-12285-4
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing sinusoidal channels of HZSM-5 for high shape-selectivity to p-xylene

Abstract: The shape-selective catalysis enabled by zeolite micropore’s molecular-sized sieving is an efficient way to reduce the cost of chemical separation in the chemical industry. Although well studied since its discovery, HZSM-5′s shape-selective capability has never been fully exploited due to the co-existence of its different-sized straight channels and sinusoidal channels, which makes the shape-selective p-xylene production from toluene alkylation with the least m-xylene and o-xylene continue to be one of the few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 49 publications
2
107
0
Order By: Relevance
“…Furthermore, the intermediate species of MTO side reaction are prone to be transformed into coke and deposited onto the surface of zeolites, causing rapid deactivation (9,10). Researchers usually add adequate amount of water to the reactants to retard the deactivation of catalyst (8). However, this leads to suppressing the methylation reaction of toluene and increasing the difficulty of industrial production.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the intermediate species of MTO side reaction are prone to be transformed into coke and deposited onto the surface of zeolites, causing rapid deactivation (9,10). Researchers usually add adequate amount of water to the reactants to retard the deactivation of catalyst (8). However, this leads to suppressing the methylation reaction of toluene and increasing the difficulty of industrial production.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the passivation of external acid sites of H‐ZSM‐5, the precise control of the crystal structure of H‐ZSM‐5 is also an effective strategy to enhance the valuable para ‐xylene selectivity. Ma et al fabricated a special H‐ZSM‐5 with sinusoidal channels predominantly opened to their external surfaces to maximize the shape‐selectivity of H‐ZSM‐5 and high para ‐xylene selectivity (>99%) was achieved in toluene methylation reaction 62 . Recently, Tsubaki et al combined this tailor‐made H‐ZSM‐5 with spinel ZnCr 2 O 4 catalyst to boost the PX synthesis from the methanol‐mediated CTA process 63 .…”
Section: Methanol‐mediated or Modified Fts Pathway For Cta Which Roumentioning
confidence: 99%
“…2 unexpectedly point out an obviously opposite result that enlarging the size along c-axis in H-ZSM-5 catalyst can result in a higher OCC catalytic activity and a better stability. It is well known that many factors in H-ZSM-5 crystal can influence the catalysis properties, such as acidities 26,29 , textural structures 27 and morphology [9][10][11][12] . On one hand, the influence of the textural structures and acid sites in our disquisitive catalysts can be excluded due to the similarity in these zeolites, as presented in Fig.…”
Section: Catalytic Behaviors Over H-zsm-5 Catalysts With Various Morpmentioning
confidence: 99%
“…It was reported that regulating the preferred orientations of the pore systems to crystal planes will cause the variety of the H-ZSM-5 morphologies, thus correspondingly affecting the diffusion resistances 5,6 . Morphology adjustment by reducing the particle size and shape with a controllable a/b or a/c "aspect ratios" is considered as an efficient route to reduce the diffusion path lengths, increase the accessibility of active sites, and finally promote catalytic activities of H-ZSM-5 samples [7][8][9][10][11][12] . In particular, constructing H-ZSM-5 catalysts with intergrowths on well-defined crystal facet opening 7,12 or nanosheet morphology with extremely short thickness along b-axis 8,9,11 , showing remarkably longer lifetime in catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%